Evaluation Report on Antyodaya Programme (1979-81) - Planning Commission (Planning Commission, 1979)
The Antyodaya Programme for the upliftment of the poorest of the poor was launched in the country first by the Government of Rajasthan on October 2, 1977. Other States viz. Himachal Pradesh, Orissa, Uttar Pradesh, Bihar and Manipur followed soon.
Programme Evaluation Organisation, Planning Commission, Government of India